Burden of podoconiosis in poor rural communities in Gulliso woreda, West Ethiopia. - Getahun Alemu; Fasil Tekola Ayele; Takele Daniel; Christel Ahrens; Gail Davey (Public Library of Science (PLoS), 2011)
Podoconiosis is an environmental lymphoedema affecting people living and working barefoot on irritant red clay soil. Podoconiosis is relatively well described in southern Ethiopia, but remains neglected in other parts of the Ethiopian highlands. This study aimed to assess the burden of podoconiosis in rural communities in western Ethiopia.A cross-sectional study was conducted in Gulliso woreda (district), west Ethiopia. A household survey in the 26 rural kebeles (villages) of this district was conducted to identify podoconiosis patients and to measure disease prevalence. A more detailed study was done in six randomly selected kebeles to describe clinical features of the disease, patients' experiences of foot hygiene, and shoe wearing practice. 1,935 cases of podoconiosis were registered, giving a prevalence of 2.8%. The prevalence was higher in those aged 15-64 years (5.2%) and in females than males (prevalence ratio 2.6∶1). 90.3% of patients were in the 15-64 year age group. In the detailed study, 335 cases were interviewed and their feet assessed. The majority of patients were farmers, uneducated, and poor. Two-third of patients developed the disease before the age of thirty. Almost all patients (97.0%) had experienced adenolymphangitis (ALA - red, hot legs, swollen and painful groin) at least once during the previous year. Patients experienced an average of 5.5 ALA episodes annually, each of average 4.4 days, thus 24 working days were lost annually. The incidence of ALA in podoconiosis patients was higher than that reported for filariasis in other countries. Shoe wearing was limited mainly due to financial problems.We have documented high podoconiosis prevalence, frequent adenolymphangitis and high disease-related morbidity in west Ethiopia. Interventions must be developed to prevent, treat and control podoconiosis, one of the core neglected tropical diseases in Ethiopia.